The Many (Still) Functional Housing Estates of Bucharest, Romania: A Viable Housing Provider in Europe s Densest Capital City. - Marin, Vera; Chelcea, Liviu (Springer Open, 2018)
Housing estates built during the post-World War II decades in many countries have followed diverging trajectories. These include maintenance and repair, demolition, doing nothing, and demolition with mixed-usage replacements. Drawing on empirical and historical material from Bucharest, Romania, a city in which 80% of the housing stock consists of socialist era housing estates, we argue that such housing continues to be viable and is even enjoying a minor renaissance, mainly through the financial efforts of residents and, occasionally, through the allocation of a certain amount of public funds. The empirical analysis illustrates that it is neither the mass character of such housing, nor its high-rise nature that creates the problems and negative image often associated with housing estates elsewhere in the world. Rather, we outline seven challenges faced by such estates: ageing of their structure and resident population, networked connectivity, energy efficiency, densification, urban planning that favours real estate agents, neglect of housing policies and housing rights, and condominium governance. The housing estates and their problems are so much a part of everyday normality in Bucharest that the local administration tends to take them for granted and has not placed them on the public agenda despite the inevitability of their structural decay at some time in the future. More than anything else, the state and the owners need to gather data in order to preempt future emergencies or continuing physical decay of this valuable housing stock.
Keywords: Wohnungswesen; Wohnsiedlung; Wohnungspolitik; Fallbeispiel